2011
DOI: 10.1007/s11595-011-0304-3
|View full text |Cite
|
Sign up to set email alerts
|

Reaction products of MgO and microsilica cementitious materials at different temperatures

Abstract: The paste was prepared by mixing MgO, microsilica and H 2 O in the presence of water reducer at different reaction ratios and temperatures, and characterized by XRD, DTA, TGA, IR, and solid-state 29Si NMR. The experimental results showed that, besides Mg(OH) 2 , magnesium silicate hydrate (M-S-H) was formed at a low temperature such as 25 and 50 ℃. At a high temperature of 100 ℃, Mg(OH) 2 can be further transformed into M-S-H completely, for instance, within ca. 1 month in an excess of microsilica. The average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 8 publications
1
21
0
2
Order By: Relevance
“…The formation of MSH as the reaction product between reactive MgO and microsilica at room temperature confirmed the findings of others (Wei et al, 2006(Wei et al, , 2011. Ongoing studies, using different source raw materials, giving a pH range of the blends of between 9.0 and 11.7, further showed that the reaction rate is significantly affected by the characteristics of the MgO, in particular its reactivity and pH (Jin, forthcoming) where the reactivity indicated the amount of brucite available for reaction and the pH determined the solubility of the microsilica in water.…”
Section: Performance In Paste Blendssupporting
confidence: 90%
“…The formation of MSH as the reaction product between reactive MgO and microsilica at room temperature confirmed the findings of others (Wei et al, 2006(Wei et al, , 2011. Ongoing studies, using different source raw materials, giving a pH range of the blends of between 9.0 and 11.7, further showed that the reaction rate is significantly affected by the characteristics of the MgO, in particular its reactivity and pH (Jin, forthcoming) where the reactivity indicated the amount of brucite available for reaction and the pH determined the solubility of the microsilica in water.…”
Section: Performance In Paste Blendssupporting
confidence: 90%
“…The exothermic peaks occur at about 850°C with no weight loss. It should account for the crystallization of M–S–H gels to form 2MgO·SiO 2 . The endothermic peak at about 400°C and the exothermic peak at about 850°C are not apparent for the samples aged at short time, indicating that the hydration of MgO are not sufficient.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been used in the field of encapsulation of nuclear or metal containing wastes and contaminant immobilization . Therefore, MgO–SiO 2 –H 2 O system has significant potential practical applications and now becomes a hot topic …”
Section: Introductionmentioning
confidence: 99%
“…The structure of M-S-H gel produced by reacting MgO and silica fume (SF) with water has recently been reported using x-ray diffraction, IR spectra, DTA-TGA-EGA and NMR studies [9][10][11]14].…”
Section: Introductionmentioning
confidence: 99%
“…The addition ofNa-HMP to the mix water has been reported to significantly improve the rheology and properties of MgO/SF pastes and mortars and this enables the production of materials with high strength, high density and low porosity [10,13].…”
Section: Introductionmentioning
confidence: 99%